FINANCIAL ADMINISTRATION OF THE UNITED NATIONS. - Payne, John B. (The Accounting Review, 1949)
Abstract This article discusses the financial administration of the United Nations. By the terms of Article 17 of the Charter the General Assembly considers and approves the budget of the United Nations and apportions the expenses among the member nations. In these respects it resembles the usual governmental legislative body which is the fund-raising and fund-granting authority for the governmental area which it serves. Also, like the usual legislative body, it has set up committees corresponding to an appropriation committee and a ways and means committee, or a committee on taxation. The Administrative and Budgetary Committee, ordinarily called the Fifth Committee, is one of the main committees of the General Assembly. It corresponds to the usual appropriation committee so far as most of this work is concerned. However, it also considers the assessment of contributions. Every resolution involving expenditure of money proposed for enactment by the General Assembly must be reviewed by the Fifth Committee which explains the effect the proposal will have upon the budget.